Design of Registration and Validation Algorithm of Member’s Personal Data - Solomia Fedushko; Yuriy Syerov (Institute of Advanced Engineering and Science, 2013)
This paper deals with the methods of verification of web-forum members’ personal data, which are implemented in the algorithm of registration and validation of personal data on web-community member. The problem of personal data verifying and method of registration in an online community is investigated. These issues have the greatest influence on efficiency rise of virtual communities functioning and the level of data authenticity in web-members’ personal profiles. Solution of these problems is possible by using computer-linguistic analysis of web-members’ posts.DOI: http://dx.doi.org/10.11591/ij-ict.v2i2.3960